Send for me [compact disc, unabridged] : a novel - Fox, Lauren (Blackstone Publishing, 2021)
An achingly beautiful work of historical fiction that moves between Germany on the eve of World War II and present-day Wisconsin, unspooling a thread of love, longing, and the powerful bonds of family.